Los tratados y la diplomacia en la antigüedad : el derecho internacional como sustento de la conquista romana - Galindo Roldán, Juan Manuel (2013)
International law, unlike the position of classical doctrine, is not an invention\nof modernity but a consequence of civilization. In this sense, this work maintains\nthat the Romans, since its early origins, have made use of the international law, constituting\nthe normal way in which the different villages interact with each other.\nThis short essay studies the different historic events of the first centuries of Rome to\nidentify how treaties and diplomacy worked as tools of legitimacy for roman conquests.